Comparing Curricula in Law and Using Innovation Lawyer Training Techniques: Kazakhstan and Russian Experience (Journal of Educational Sciences, 2022)
The major distinctive features of today’s universities include the ability to generate knowledge andprovide an efficient training system for top qualification human resources which in its turn, requires improved academic curricula and extended use of innovation techniques in the training process. Currently,one of the drivers that shapes high quality education is represented by the efficient academic activitiesthat involve the use of innovation techniques. The article provides a comparative analysis of curricula inlaw in Kazakh and Russian institutions of higher education to identify the approaches to improvement ofthe training offered to future lawyers, while describing the importance of innovation techniques in training students seeking a degree in law, aimed at higher training efficiency. The key criteria relied on in thecomparative analysis include reviewing the academic content and mandatory disciplines studied at theuniversity level, as well as the choices made by students. The scientific novelty of the research work is instudying the peculiar features of the curricula for a bachelor degree course in Legal Studies, Law, as exemplified by Kazakh and Russian universities. The research findings suggest that the universal academicprocess, wherein special attention is paid to improved curricula in law, as well as to the extended use ofinnovation techniques, may significantly increase training efficiency.Key words: curriculum, universal academic process, innovation techniques, legal education.